Agribusiness entrepreneurial intention: The roles of psychological traits, situational factors, perceived behaviour control and entrepreneurial education / Aki @ Zaki Aman - Aman, Aki @ Zaki (Institute of Graduate Studies, UiTM, 2018)
Agribusiness is one of the important elements in a country's economic development. Economists agree that agribusiness is one of the contributors to the country's growth and provides employment opportunities. Various programmes have been introduced by the Malaysian government for developing entrepreneurs among university graduates. However, the rate of involvement by graduates is still below the target. Moreover, there are limited studies on agribusiness entrepreneurial intention among university graduates. Therefore, studies on agribusiness entrepreneurial intention among university graduates are essential to formulate better action plans. The objective of this study is to understand the influence of psychological traits, situational factors, perceive behaviour control and entrepreneurial education on agribusiness entrepreneurial intention amongst university graduates. An integrative framework was developed to explore and understand the predicting factors on agribusiness entrepreneurial intention among university graduates comprising psychological traits, perceived situational factors and perceived behavioural control. Entrepreneurial education was used as a moderating variable between studied variables…